Unbound how inequality constricts our economy and what we can do about it - Boushey, Heather, 1970- (Harvard University Press, 2019)
"Many fear that efforts to address inequality will undermine the economy as a whole. But the opposite is true: rising inequality has become a drag on growth and an impediment to market competition. Heather Boushey breaks down the problem and argues that we can preserve our nation's economic traditions while promoting shared economic growth"--